Upaya Tumbuhkan Perilaku Budi Pekerti Baik Kepada Anak Panti Asuhan Al Washliyah Kota Binjai Provinsi Sumatera Utara - Annisa Aulia; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The orphanage is a social institution that aims to shape the development of children, such as orphans, orphans, orphans, abandoned children.  Children will feel safe, receive support, attention if they feel their presence is accepted by all parties.  However, in reality these expectations are difficult to achieve due to lack of attention from caregivers, facilities, unable to form warm relationships with other people.  Through service activities, students do service to the children of the Al-Washliyah Orphanage, Kec.  Binjai City, Binjai.  Beginning with institutional observations.  There were several problems with children, such as frequent fights, bullying, harsh words to others, and lack of hygiene.  The intervention method used in this service is the Mezzo Intervention by Zastrow consisting of: Intake/Engagement, Assessment, Planning, Implementation, Evaluation, and Termination.  The results of the service are able to foster good character behavior through sharing session programs, self-introspection letters, learning groups, socializing the impact of bullying, making rules, sanctions.  The implications of this service activity are able to contribute to forming a good personality, attitude, tolerance for orphans.